Prevalence and determinants of erectile dysfunction among type 2 diabetes mellitus patients at selected government hospitals in gurage zone: A cross-sectional study - Seid Abrar Abdlshikure; Aklilu Getachew Mamo; Bisrat Fikadu; Abdulber Seid (PLoS ONE, 2025)
Background Erectile dysfunction (ED) is often not recognized in men with type 2 diabetes mellitus (T2DM), despite the prevalence of the disease. Early diagnosis of ED in T2DM is very important for effective treatment and prevention of serious complications such as cardiovascular events.This study investigates the prevalence and determinants of ED among T2DM patients at selected government hospitals in the Gurage Zone. Methods We conducted a study in three public hospitals from September 1 to December 30, 2020. 204 diabetic men were selected using consecutive sampling. ED was evaluated utilizing the International Index of ED-5. Glycated hemoglobin (HbA1c) and lipid levels were analyzed utilizing a Cobas 600 clinical chemistry analyzer. The data was analyzed using the Statistical Package for Social Sciences-20. Results ED was observed in 156 (76.5%) diabetic males. Independent predictors of ED included age above 40 years, alcohol consumption, khat chewing, overweight [Body mass index (BMI) ≥ 25 kg/m2], obesity (BMI ≥ 30 kg/m2), a diabetes duration of more than 5 years, uncontrolled diabetes (HbA1c > 7%), elevated low-density lipoprotein (LDL), and high total cholesterol levels (P < 0.05). Conclusion The study confirmed a high prevalence of ED among males with T2DM in the study settings. Consequently, clinicians should adopt preventive measures and focus on identifying the factors associated with ED in these patients.